Structural Characterizations, Optical and Electrical Properties of Zinc Oxide Thin Films Grown by Atomic Layer Deposition Method - Khalass, Talal; Sarem, Ammar (Latakia University Journal -Basic Sciences Series, 2013)
In this paper we present the structural, optical and electrical characteristics of ZnO thin films grown for different parameters by the atomic layer deposition (ALD) method. The films were grown on glass and silicon substrates at low temperatures. We used diethyl-zinc (DEZn) and deionized water as zinc and an oxygen sources, respectively. Measurements of surface morphology, photoluminescence at room temperature (RT PL) and Hall Effect were made for ZnO layers. The films obtained at 130°C show the highest carrier concentration (1.1×1019 cm-3) and the lowest resistivity (2.84×10-2 Wcm). The films exhibit mobility up to 19.98 cm2/Vs that we associate to the technological process used. نقدم في هذه الورقة الخصائص البنيوية والضوئية والكهربائية لأفلام رقيقة من أكسيد الزنك تمت تنميتها من أجل بارامترات مختلفة بوساطة طريقة الترسيب الذري الطبقي (ALD) . وقد نميت هذه الأفلام على ركائز من الزجاج والسيلكون عند درجات حرارة منخفضة. استخدمنا ثنائي إيتيل الزنك(diethyl-zinc) والماء منزوع الأيونات كمصادر للزنك والأكسجين، على التوالي. أجريت قياسات مورفولوجيا السطح، والتألق الضوئي في درجة حرارة الغرفة ومفعول هول لطبقات من أكسيد الزنك. وقد بينت الدراسة أن الأفلام التي تم الحصول عليها عند درجة حرارة130°C تظهر أعلى تركيز للحاملات(1.1×1019 cm-3) وأقل مقاومة(2.84×10-2 Wcm) . كما أظهرت الأفلام حركية تصل إلى 19.98 cm2/Vs وأنها ترتبط مع عملية التكنولوجيا المستخدمة.